Is Crisis the Only Way to Put Innovators in Charge in Hierarchical Firm? - Torkanovskiy, Evgeny Petrovich (Open Science Journal, 2019)
The way innovators are recruited and treated within organization impacts the company’s ability to innovate. Based on literature review this research finds evidence that contrary to Schumpeterian assumptions that large companies through concentration of resources play leading role in innovation process, big hierarchical firms may fail to innovate due to recruiting patterns. Corporate hierarchy, unlike markets, tends to maintain permanent and total control of the employees and to punish and push out the least controllable. The manager has personal interest to hire and promote the most controllable employees, the ones least threatening to the manager’s status and not the most creative or innovative. This inherent feature of any hierarchy may make it unable to recruit, promote innovators and thus maintain efficient innovation process. It leads to accumulation of innovation errors and lags and to regular crises within hierarchy and of hierarchy itself due to the lack of progress and innovation. However, the crises may lead to management renewal and innovators’ promotion to decisive positions and roles. On the other hand, it means that in order to adopt and implement innovations a hierarchy requires internal or external shocks, sometimes even self-generated or exaggerated.